Pertolongan Pertama Keracunan Makanan dengan Metode PADAM Berbasis Edukasi Kesehatan dan Vidio Demonstrasi pada Anggota PMR di MAN 4 Kediri - Didit Damayanti; Pria Wahyu Romadhon G; Devita Anugrah Anggraini (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
School groups are part of society that must receive important attention. School student groups are at high risk of food poisoning caused by free snacks that do not pay attention to hygiene and lack of food sanitation. Food poisoning can cause morbidity and mortality if not treated properly. Improving the health status of the school community can be done through various activities, one of which is by providing Food Poisoning Assistance Training. Students at MAN 4 Kediri are a group of teenagers in society who are at risk of health problems due to dynamic activities. First aid for food poisoning with educational methods and video demonstrations of the PADAM technique can be treatment that can be given immediately. Community service activities in the form of educational training and video demonstrations about first aid for food poisoning with the PADAM technique for members of PMR MAN 4 Kediri are very positive activities to carry out in order to disseminate health knowledge so as to increase the knowledge and ability of each student in providing first aid for food poisoning.